Optimizing Medical Equipment Lifecycle Management: A Qualitative Study of Biomedical and Radiological Technicians' Roles in Long-Term Care and Medical Supply Settings - Ayad Munaished Aldhufairy; Hmad Salem Kaleif Algameely; Thamer Amer Sultan Algushm; Mutaib Awad Al-Mutairi; Salah Sabbar Aldhaferi; Yousef Hamidi Al-Mutairi; Mohammed Huri Alanazi; Mushahhin Hamoud Alshammari (International Journal of Medical Toxicology and Legal Medicine, 2024)
Medical equipment lifecycle management is a critical aspect of healthcare delivery, particularly in long-term care and medical supply settings. Biomedical and radiological technicians play vital roles in ensuring the optimal functioning, maintenance, and disposal of medical devices. This qualitative study explores the experiences and perspectives of these technicians to identify best practices, challenges, and opportunities for improvement in medical equipment lifecycle management. Semi-structured interviews were conducted with a purposive sample of seven technicians from long-term care and medical supply settings. Thematic analysis revealed four main themes: (1) proactive maintenance and calibration, (2) effective communication and collaboration, (3) challenges in managing aging equipment, and (4) opportunities for training and professional development. The findings highlight the importance of preventive maintenance, interprofessional teamwork, strategic planning for equipment replacement, and ongoing education for technicians. Implementing these strategies can optimize medical equipment lifecycle management, leading to improved patient care, cost savings, and environmental sustainability. Further research is needed to develop and evaluate targeted interventions to support technicians in their critical roles.